(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2022)
The current descriptive-analytic study aimed at identifying the effects of the organizational climate on the workers creativity at the Company of SONELGAZ-DJELFA’s District throughout the following elements: (organizational structure, leadership, the style of communication, , technology and incentives) , at the significant level of (α≤0.05 ). A questioner of 38 questions containing all the elements of the organizational climate and movement’s creativity was made. The study was implemented on a sample of 32 elements. The study found that there is an impact of the organizational climate in its different dimensions on creativity in the institution under study. Keywords : organizational climate, innovation, organizational structure, leadership, communication, technology, incentives